Management of distal limb skin defects in dogs and cats - TSIOLI (Β. ΤΣΙΩΛΗ), V.; DERMISIADOU (Ε. ΔΕΡΜΙΣΙΑΔΟΥ), E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Skin defects on the lower limb are common and their management is usually challenging. All trauma patients should be initially assessed for concurrent injuries and stabilized. Debridement and cleansing is performed in all wounds. The most important factors for decision making on wound closure are the wound size, the extent of soft tissue damage, the presence of contamination and impaired perfusion. Primary closure is the preferred choice although; it is seldom applicable in wounds on the distal limbs. Delayed primary closure, secondary closure or second intention healing can be undertaken under certain circumstances in such wounds. When these options are not feasible local pedicle flaps, axial pattern flaps, distant flaps, grafts, muscle or myocutaneous flaps and microvascular free tissue transfer can provide coverage.